(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
درسنا في هذا البحث مسألة تقريب الدوال العقدية من فضاء ليبيغ الموزن حيث و (وزن ماكنهوبت)، إلى دوال كسرية متعلقة بكثيرات حدود p – فابير وذلك على أسرة واسعة من المنحنيات تدعى منحنيات كارلسون، كما ويعد هذا العمل بمثابة متابعة لما قام به الباحثان Israfilov و Testici عام 2014 في [4]، حيث درسا تقريب الدوال العقدية من فضاء سميرنوف الموزن على مناطق محاطة بمنحنيات كارلسون. In this research, we have studied the issue of approximation of complex functions from weighted Lebesgue space ; and (Mukenhoupt weight) to rational functions by using p- Faber polynomials on large group of curves, which called Carlson curves. This is also considered as a follow-up to the work done by researchers: Israfilov and Testici in 2014 [4], where they studied approximation of functions from weighted Smirnov space on domains with a Carlson curve boundary.